Loan Interest of KUR at PT Pegadaian UPC Trenggalek: The Role of Cross Selling, Word of Mouth, and Social Media - Kartika, Putri Dwi Agnes; Muslih, Basthoumi (Universitas Nusantara PGRI Kediri, 2024)
Research aim: The purpose of this study was to test and analyze the effect of cross selling, word of mouth, and social media partially and simultaneously on the interest in loan people's business credit (KUR) at PT Pegadaian UPC Trenggalek. Design/Method/Approach: This research is a type of quantitative research with a causality approach. The population of this study were all customers at Pegadaian UPC Trenggalek, this research instrument used a questionnaire involving 140 KUR customer respondents at Pegadaian UPC Ttrenggalek. The sampling technique uses simple random sampling, and the data analysis technique uses multiple linear regression tests. Data processing was carried out using SPSS 23. Research Finding: The results of this study prove that cross selling, word of mout, and social media partially and simultaneously affect KUR interest at Pegadaian UPC Trenggalek. Theoretical contribution/Originality: This research contributes to understanding and provides insight related to cross selling, word of mouth, social media and interest in KUR loans at Pegadaian. Practitionel/Policy implication: For companies, this research can be an illustration in the strategy of increasing interest in KUR loans at Pegadaian. Research limitation: This research only discusses cross selling, word of mouth, social media. Time constraints for distributing questionnaires which must involve 140 respondents but only 100 respondents were collected. Keywords: Cross Selling, Word of Mouth, Social Media